Prevalence of Accidents and Injuries and Related Factors of Fishermen Fishing Offshore in the North of Vietnam - Van Tam Nguyen; Bao Nam Nguyen; Truong Son Nguyen; Quynh Chi Tran; Van Hoa Ho; Hai Ha Nguyen (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Seafaring, particularly offshore fishing, exposes fishermen to various occupational risks leading to diseases and injuries. This study aimed to determine the prevalence of occupational risks, injury accidents, and contributing factors among offshore fishers in North Vietnam, to develop evidence-based recommendations to enhance their safety and well-being. Methods: A cross-sectional study was conducted involving 420 fishermen with a minimum of two years of experience. Interviews were conducted between 2018 and 2020. Results: The findings indicated that there is a 41.7% prevalence of accidents and an average injury rate of 280.2 per person per year. Most incidents occurred at night with 104 cases (59.4%), slips and falls 48 cases (27.4%), broken winch lines 40 cases (22.9%), and ship collisions 14 cases (8.0%) being the primary causes. The most common injuries included soft wounds in 92 cases (52.5%) and sprains/dislocations in 14 cases (8.0%). Fishermen with fewer than 10 years of experience exhibited a higher accident risk (odds ratio = 1.54; 95% confidence interval: 1.05-2.72), as did those in the role of a fisherman (odds ratio: 1.68; CI: 0.97-2.94) and those working without labor protection (odds ratio: 3.68; CI: 1.05-12.93). Conclusion: Lack of labor protection equipment increased the risk by 3.68 times, and fishermen in the friend group had a 2.02 times higher risk of injury. Addressing these risks requires adherence to labor protection regulations and safe working procedures.